Messages of Peace and Morality in the Novels Kazak dan Penyerbuan by Leo Tolstoy - Yuriananta, Renda; Sukardi, Mochamad Ighfir; Wanaeloh, Arsiya (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2025)
Leo Tolstoy (1828–1910) is widely recognized as one of the most influential figures in Russian literature, whose works have had a lasting impact on the global literary canon. This study focuses on a critical analysis of two of his early novels, Kazak dan Penyerbuan, composed during Tolstoy’s service in the Caucasus. Despite their seemingly slow narrative progression, these works employ a deliberate pacing that reflects both the existential stillness of military life and the moral introspection characteristic of Tolstoy’s evolving philosophy. This paper addresses the problem of how Tolstoy articulates the ideals of peace and morality within the structure of narrative and character development in these early works. Utilizing a close reading method combined with historical-literary contextualization, the study identifies three major elements: Tolstoy’s thematic construction of peace, the mediation of moral reflection through dialogue and narrative events, and his technique of narrative immersion. By situating Kazak and The Invasion within the broader historical context of 19th-century Russian imperial expansion into the Caucasus, this analysis contributes to a deeper understanding of Tolstoy’s early engagement with ethical and existential questions. The study proposes that these early texts not only anticipate Tolstoy’s later moral philosophy but also offer a foundational perspective for mapping Tolstoy’s evolving literary and ideological trajectory within Russian literature.